2008
DOI: 10.1016/j.drugalcdep.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Partner aggression among men and women in substance use disorder treatment: Correlates of psychological and physical aggression and injury

Abstract: This study examined intimate partner aggression in a sample of 489 participants enrolled in substance use disorder treatment, and expands on prior research by including measures of various forms of aggression, a mixed gender sample (76% men, 24% women), and measurement of several potential risk domains. Aggression measures included both participant-to-partner and partner-to-participant psychological aggression, physical aggression and injury. Analyses focused on the role of distal and proximal risk factors, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
91
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 70 publications
15
91
0
4
Order By: Relevance
“…First, younger individuals have frequently been shown to have higher rates of psychological aggression (Chermack et al, 2008) and physical aggression (George, 1999;Moore et al, 2008). Second, although gender differences often have been found to be negligible for physical aggression in partner relationships in SUD samples (e.g., Chermack et al, 2008;Chermack et al, 2001;Walton et al, 2003), there is some evidence to suggest that this fi nding may not hold true for nonpartner violence (NPV). For example, Chermack and colleagues (2001) found that men in SUD treatment had higher rates of NPV than women (66.7% and 39.5%, respectively), and Walton and colleagues' (2007) emergency department-based study found that men were twice as likely as women to engage in nonpartner aggression.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…First, younger individuals have frequently been shown to have higher rates of psychological aggression (Chermack et al, 2008) and physical aggression (George, 1999;Moore et al, 2008). Second, although gender differences often have been found to be negligible for physical aggression in partner relationships in SUD samples (e.g., Chermack et al, 2008;Chermack et al, 2001;Walton et al, 2003), there is some evidence to suggest that this fi nding may not hold true for nonpartner violence (NPV). For example, Chermack and colleagues (2001) found that men in SUD treatment had higher rates of NPV than women (66.7% and 39.5%, respectively), and Walton and colleagues' (2007) emergency department-based study found that men were twice as likely as women to engage in nonpartner aggression.…”
mentioning
confidence: 87%
“…We expected that all substances would be bivariately related to aggression, with alcohol and cocaine being the most robust predictors of aggression in multivariate analyses. Finally, based on previous studies on depression and aggression (e.g., Chermack et al, 2008;Walton et al, 2007), we expected that depressive symptoms would be associated with aggression outcomes.…”
mentioning
confidence: 99%
“…In humans, substance abuse has been associated with weapon-related violence and homicide (Spunt et al 1998;Madan et al, 2001;Hagelstam and Hakkanen 2006), intimate partner aggression, including partner-directed physical and psychological aggression (O'Farrell and Fals-Stewart 2000;Chermack et al 2008), sexual abuse (El-Bassel et al 2001), and child abuse (Haapasalo and Hamalainen 1996;Mokuau 2002;Walsh et al 2003). Collectively, drug-related violence leads to family system dysfunction and incarceration (Krug et al 2002), creating significant societal concerns.…”
Section: Natural Versus Artificial Rewardmentioning
confidence: 97%
“…Andersom geldt ook dat partnermishandeling relatief prevalent is bij cliënten met stoornissen in het gebruik van een middel. Van de mannen en vrouwen die in behandeling komen voor hun problematische middelengebruik rapporteert 35-60 % in het afgelopen jaar geweld te hebben gebruikt naar de partner (Chermack et al 2008;Chermack en Blow 2002;Kraanen et al 2013Kraanen et al , 2014O'Farrell en Murphy 1995;Stuart et al 2002;Vedel 2007). Kraanen et al (2014) toonden aan dat partnergeweld (pleger-en/of slachtofferschap) bij mannen in deze groep voorspeld werd door de een stoornis in het gebruik van alcohol in combinatie met een aan stoornis in het gebruik van cannabis en/of cocaïne.…”
Section: Partnermishandeling En Middelengebruik: Hoe Vaak Gaat Dit Saunclassified